2010
DOI: 10.1111/j.1742-4658.2010.07582.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a glycoside hydrolase family 6 enzyme, CcCel6C, a cellulase constitutively produced by Coprinopsis cinerea

Abstract: The basidiomycete Coprinopsis cinerea produces the glycoside hydrolase family 6 enzyme CcCel6C at low and constitutive levels. CcCel6C exhibits unusual cellobiohydrolase activity; it hydrolyses carboxymethyl cellulose, which is a poor substrate for typical cellobiohydrolases. Here, we determined the crystal structures of CcCel6C unbound and in complex with p‐nitrophenyl β‐d‐cellotrioside and cellobiose. CcCel6C consists of a distorted seven‐stranded β/α barrel and has an enclosed tunnel, which is observed in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 43 publications
0
29
1
1
Order By: Relevance
“…670 The authors suggested the structure was an additional example of a GH6 CBH based on prior characterization on PASC despite the high sequence homology with the H. insolens EG Cel6B. However, in the current study, CcCel6C was tested for activity on CMC and demonstrated specificity for the substrate unlike any other GH6 CBH.…”
Section: Discussionmentioning
confidence: 69%
“…670 The authors suggested the structure was an additional example of a GH6 CBH based on prior characterization on PASC despite the high sequence homology with the H. insolens EG Cel6B. However, in the current study, CcCel6C was tested for activity on CMC and demonstrated specificity for the substrate unlike any other GH6 CBH.…”
Section: Discussionmentioning
confidence: 69%
“…Cellulose is a polysaccharide formed by the polymerization of several hundreds to thousands of β‐(1,4)‐ d ‐glucose units. Moreover, cellulose is a predominant component of the plant cell wall . Native celluloses are insoluble materials that can be degraded into small cellodextrin or glucose by glycoside hydrolases (GHs) .…”
Section: Introductionmentioning
confidence: 99%
“…The entire genomic sequence of C. cinerea has been reported [2]. The fungal genome contains many genes coding for enzymes that participate in plant cell biomass degradation, and we have previously reported the crystal structures of cellobiohydrolases [3][4][5]. C. cinerea possesses a gene, CC1G_07166, which encodes a protein homologous to PaGluc131A (42% identity).…”
Section: Introductionmentioning
confidence: 99%